The efficacy and safety of diuretics on extracorporeal shockwave lithotripsy treatment of urolithiasis: A systematic review and meta analysis. Issue 25 (19th June 2020) - Dong, Liying; Wang, Fengyao; Chen, Hongyan; Lu, Youyi; Zhang, Yong; Chen, Linjing; Cui, Yuanshan
Abstract: Background: The aim of this systematic review and meta-analysis was to demonstrate the efficacy and safety of diuretics on extracorporeal shockwave lithotripsy (SWL) treatment of urolithiasis. Methods: The databases MEDLINE, EMBASE, and the Cochrane Controlled Trial Register of Controlled Trials from January 1980 until November 2019 were searched to identify randomized controlled trials that referred to the use of diuretics on extracorporeal SWL treatment of urolithiasis. Results: Six randomized controlled trials containing 1344 patients were included in this meta-analysis, which compared diuretics with placebo on extracorporeal SWL treatment of urolithiasis. In the analysis, we found that diuretics on extracorporeal SWL treatment were more effective for the management of urinary stones. Compared with placebo, patients who received diuretics during extracorporeal SWL treatment had significantly higher successful stone clearance rate (Odds ratio; 1.73, 95% confidence interval (CI); 1.35 to 2.21, P  < .0001), higher stone fragmentation rate (odds ratio; 2.83, 95% CI; 1.30 to 6.16, P  = .009), less average number of sessions per stone (mean difference; –0.13; 95% CI, –0.25 to –0.01, P  = .03) and similar average number of shocks per stone (mean difference; –126.89; 95% CI, –394.53 to 140.76, P  = .35). Conclusion: This systematic review and meta-analysis indicates that diuretics during extracorporeal SWL was effective in the management of urolithiasis with lower risk of complications.